Parents' Expectations for Islamic Schools: Multi-Site Study in Al Falah High School, Muhammadiyah 2 High School, and Al Hikmah High School in Surabaya - Nur Halima; Sri Suprapti (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
This study aims to find out what parents expect from Islamic-based schools in Al Falah High School, Muhammadiyah 2 High School, and Al Hikmah High School in Surabaya.This study uses a qualitative approach with a multi-site design. The subjects in this study were parents, principals, deputy principals, teachers, and students at Al Falah High School, Muhammadiyah 2 High School, and Al Hikmah High School in Surabaya, Indonesia. Selection of informants with a purposeful technique sampling and snowball sampling Data collection was carried out through in-depth interviews, participant observation, and documentation studies. Data analysis used a modified analytic analysis method. While data validity is used to reveal credibility, transferability, dependability, and confirmability. The results of this study indicated the expectation included students’ output, which refers to having a strong faith, having awareness, and obedience in practicing Muslim faith tenets and its good deed of sunnah. Moreover, the students’ outcomes are defined as practicing the Muslim faith in the real life in society, becoming imam in salat, and becoming a leader in certain Islamic events in society. This study concluded that the parents’ expectation was fulfilled that their children have a good religious character. Hence, this research is expected to develop a renewal of Vroom's theory in school management